Review of the Adequacy of the Fund's Precautionary Balances. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2018)
This paper reviews the adequacy of the Fund's precautionary balances, using the framework approved by the Board in 2010. The review takes place on the standard two-year cycle and assesses developments since the last review in 2016.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet